Electrical Characteristics and pH Response of a Parylene-H Sensing Membrane in a Si-Nanonet Ion-Sensitive Field-Effect Transistor - Bo Jin; Ga-Yeon Lee; ChanOh Park; Donghoon Kim; Wonyeong Choi; Jae-Woo Yoo; Jae-Chul Pyun; Jeong-Soo Lee (Sensors, 2018)
We report the electrical characteristics and pH responses of a Si-nanonet ion-sensitive field-effect transistor with ultra-thin parylene-H as a gate sensing membrane. The fabricated device shows excellent DC characteristics: a low subthreshold swing of 85 mV/dec, a high current on/off ratio of ~107 and a low gate leakage current of ~10−10 A. The low interface trap density of 1.04 × 1012 cm−2 and high field-effect mobility of 510 cm2V−1s−1 were obtained. The pH responses of the devices were evaluated in various pH buffer solutions. A high pH sensitivity of 48.1 ± 0.5 mV/pH with a device-to-device variation of ~6.1% was achieved. From the low-frequency noise characterization, the signal-to-noise ratio was extracted as high as ~3400 A/A with the lowest noise equivalent pH value of ~0.002 pH. These excellent intrinsic electrical and pH sensing performances suggest that parylene-H can be promising as a sensing membrane in an ISFET-based biosensor platform.